STATE SUPPORT OF SMALL AND MEDIUM ENTERPRISES IN FORMING NEW TECHNOLOGICAL BASE OF INDUSTRY - A. К. Kurilo (Вестник Российского экономического университета имени Г. В. Плеханова)
The article shows the current state of small and medium entrepreneurship in the Russian Federation. The comparison of innovation figures of business of different size in Russia and EU countries was conducted. The research was able to identify the long-term laws of the development of small and medium business in conditions of cyclic renewal of the technological base of industry and achievements that take into account such laws of supply in upgrading the system of state support. During investigation of figures of small business development it was empirically confirmed that there was a link between the level and character of innovation activity of small and medium enterprises and stages of developing a new technological structure in economy. On the basis of statistical data the role of business of different sizes was identified on phases of the long wave of economic development. The article describes the present system of state support of small and medium enterprises in the Russian Federation and shows drawbacks of such support of small and medium business and puts forward steps aimed at its improvement in conditions of necessity to form a new technological base of industry. The author substantiates the approach to the development of the system of state support of small and medium enterprises, which take into account the specific features of its development on certain stages of the long wave under the influence of renewal of the technological base of industry.